Brooklyn nine-nine. Season 7 [videorecording (DVD)] - Goor, Daniel J., 1975-; Schur, Michael, 1975- (Universal Pictures Home Entertainment, 2020)
Brooklyn's finest and funniest police officers make their triumphant return in the sixth season of the critically-acclaimed and fan-adored comedy series. From Jake and Amy's romantic honeymoon, with Holt, a return to the glory days of Hitchcock and Scully, and Gina's hot moves and big news, the Nine-Nine is #goals.